Editorial - Cock, I.E. (Pharmacognosy Communications)
With this issue, Pharmacognosy Communications enters into its fifth year. In our first 4 years of publication, Pharmacology Communications has published 14 review articles, 121 original research studies and 29 short communications at an average of 10.3 published manuscripts per issue. We strive for publication of high quality studies as is reflected but our acceptance rate, which has been approximately 35 % each year that we have published.